Critical success factors for start-up companies - Sparrius, Stephan (My University, 2011)
The South African Futures Exchange (SAFEX) implemented anonymous trading on all their futures contracts on 26 May 2009. The impact of market design on market liquidity is still not well understood. Some markets, e.g. Hong Kong Stock Exchange, disclose broker mnemonics whereas in other markets, e.g. New York Stock Exchange, conceal broker mnemonics. The degree of trader anonymity is a potentially important determinant of market quality. Institutional traders are often said to prefer an anonymous environment because they do not want to publicly disclose their trading needs (Schwartz and Steil 1996). On the other hand, however, anonymity allows traders with inside information about a company to remain unidentified. The problem is that we do not know how anonymity has impacted market liquidity on SAFEX. This study examines the impact on market liquidity due to the removal of broker mnemonics on SAFEX by examining the changes in bid-ask spreads, price volatility and trading volume on the near to expiry ALSI futures contract before and after SAFEX implemented anonymous trading. In order to gain the necessary insights into the intraday liquidity of the ALSI futures contract, high frequency data is required. Therefore, the sampling approach captured each and every trade that was executed against the near to maturity ALSI futures contract for a sample period of three months before and three months after SAFEX changed over to anonymous trading, i.e. from 2 March 2009 to 20 August 2009. Details of intraday trade time, trade price and trade quantity was extracted to calculate bid-ask spreads, volatility and volume. Bid-ask spreads, volatility and volume were calculated for minute intervals and then averaged across each day to produce one observation for each day. The research found that:  Bid-ask spreads have dropped significantly after the introduction of anonymous trading on SAFEX. But after controlling for changes in volatility and volume, since the lower bid-ask spreads may be in part iii driven by changes in these variables, the decrease in bid-ask spreads is no longer significant.  Bid-ask spreads and price volatility have a statistically significant positive relationship. Volatility has dropped significantly after the introduction of anonymous trading on SAFEX.  Bid-ask spreads and trade volume have a negative relationship but this finding is not statistically significant. Volume has dropped significantly after the introduction of anonymous trading on SAFEX.
MBA - WBS
Keywords: Success factors; Small businesses